OPTIMALIZE TEACHING READING COMPREHENSION ON DESCRIPTIVE TEXT BY USING MAKING CONNECTIONS STRATEGY AT GRADE 8 OF JUNIOR HIGH SCHOOL - Wira Jaya Hartono (Universitas Negeri Medan, 2020)
Abstract: Optimalize Teaching Reading Comprehension On Descriptive Text By Using Making Connections Strategy At Grade 8 Of Junior High School. The research was conducted to find out the effect of Making Connections strategy on students’ reading comprehension of descriptive texts. The design of this research was quasi experimental – one group pretest posttest design. The total population of this research was 182 of XI grade students of SMP Dharma Loka Pekanbaru 2019/2020 academic year which divided into six classes then one class was chosen by random sampling as sample. Reading comprehension test was used as research instrument. Then, the data were analyzed using t-test by using SPSS. The result o this research shows that There is significant effect on students’ reading comprehension of descriptive text.Keywords: Teaching Reading, Making Connections Strategy (Text-to-self, Text-to-text,Text-to-world) , Descriptive textAbstrak: Mengoptimalkan Pembelajaran Pemahaman Membaca pada Teks Deskriptif dengan Menggunakan Strategi Making Connections di Kelas 8 SMP. Penelitian ini bertujuan untuk mengetahui pengaruh penggunaan strategi Making Connections dalam kegiatan membaca terhadap pemahaman membaca siswa. Desain penelitian ini adalah penelitian kuasi – one group pretest posttest design dengan sampel penelitian ini yaitu siswa kelas VIII SMP Dharma Loka Pekanbaru tahun ajaran 2019/2020 lalu dipilih secara cluster random sampling. Tes pemahaman membaca digunakan sebagai instrument penelitian. Hasil penelitian menunjukkan bahwa (1) kelompok siswa yang diajarkan dengan strategi Making Connections memiliki kemampuan membaca teks deskripsi yang lebih. Kesimpulannya, strategi Making Connections memiliki hasil yang signifikan terhadap kemampuan siswa dalam pemahaman membaca teks Deskriptif.Kata Kunci: Pemahaman Bacaan, Strategi Making Connections (Text-to-self, Text-to-text,Text-to-world) , Deskriptif teks